(untitled) - Lustbader, Eric; 1927-2001.; Ludlum, Robert (New York, 2013)
"Jason Bourne is back in this new novel in Robert Ludlum's legendary series written by New York Times bestselling author Eric Van Lustbader"--
""When Director Yadin learns of a mysterious connection between Ouyang Jidan, a senior member of China's Politburo, and a recently deceased Mexican drug lord, he asks Jason Bourne to investigate." --Provided by the publisher"--
Adult.
Adult.
Keywords: Adventure fiction; Spy stories; Fiction; Fiction; Fiction; Intelligence officers; Bourne, Jason (Fictional character); Terrorists